T142. - Deweer, Mark; Verstraete, Dries (Zwevegem-Otegem : Deweer Art Gallery Zwevegem - Otegem, 2005)
Antille, Emmanuelle ; De Cordier, Louis ; Denicolai, Simona ; Dheedene, Stefaan ; Dumas, Charlotte ; Ginneberge, Isabel ; Laurette, Matthieu ; De Leener, Eva ; Mannaerts, Valérie ; Provoost, Ivo ; Stolle, Bart ; Wauman, Andy
biog., ind. tent., gr. tent. p. 54-64
Engels
Nederlands
Exhibition. T142. Deweer Art Gallery Zwevegem - Otegem, 18.09.2005 - 06.11.2005.
boek